Students' Career and Education Decisions and Thailand’s Strategic Framework for Human Resource Development of the 20-year Period: A Case Study of Kongthong Wittaya School, Nakhon Pathom Province - Tuntiyawongsa, Orasa; Meetaworn, Kamonnat; Kidroub, Pattama (Journal of Research Methodology, 2023)
The objectives of this research were to analyze the agreement between high school students’ career choice and further education with the Thailand 20-year human resource development strategy framework (2017-2036), to measure their attitude on STEM skills, and to analyze factors affecting career choice and further education. Data from 300 Grade 7 students at Kongthong Wittaya school, Nakhon Pathom, Thailand were collected by interviews and analyzed by descriptive statistics and probit modeling. Fifty-nine percent of students wanted to study subjects that need intensive STEM skills; however, only 37% wanted to pursue a career with intensive STEM skills. The students also had a positive attitude toward STEM skills. The students’ field of study they wish to pursue was significantly related to their future occupation. Finally, the students’ gender, attitude towards STEM skills, and future career aspirations were statistically correlated with the field of study, while parent's and idol’s occupations had no significant relationship with the field and career that the students wished to pursue.